Immunological Adverse Events After Autologous Hematopoietic Stem Cell Transplantation in Systemic Sclerosis Patients - Strunz, Patrick-Pascal; Froehlich, Matthias; Gernert, Michael; Schwaneck, Eva Christina; Fleischer, Anna; Pecher, Ann-Christin; Tony, Hans-Peter; Henes, Joerg Christoph; Schmalzing, Marc (Frontiers in Immunology, 2021)
Autologous hematopoietic stem cell transplantation (aHSCT) represents an effective treatment for systemic sclerosis (SSc), but it also can cause immunological adverse events (iAE). Therefore, we aimed to determine the frequency of iAEs (engraftment syndrome (ES) and secondary autoimmune disorders (sAD)) and to identify potential risk factors for their development in a retrospective analysis on 22 patients similar transplanted due to SSc. While nine patients (41%) suffered from engraftment syndromes, seven secondary autoimmune disorders occurred in six patients (27%). Patients who developed ES were older in our cohort (52.45 years vs. 42.58, p=.0433, Cohen’s d=0.86) and cardiac involvement by SSc was associated with development of ES (OR=40.11, p=.0017). Patients with manifestation of sAD had a higher mRSS reduction after aHSCT (90.50% vs. 60.00%, p=.0064, r=0.65). Thus, IAEs are common after aHSCT for SSc and can occur in different stages during and after aHSCT with characteristic clinical manifestations. Good cutaneous response after aHSCT might be considered as risk factor for sAD and higher age at aHSCT as well as cardiac involvement as risk factors for the development of ES, respectively.